Single dose oral rofecoxib for acute postoperative pain in adults. - Bulley, S; Derry, S; Moore, R; McQuay, H (2009)
BACKGROUND: Editor's note: The anti-inflammatory drug rofecoxib (Vioxx) was withdrawn from the market at the end of September 2004 after it was shown that long-term use (greater than 18 months) could increase the risk of heart attack and stroke in a study of secondary prevention of adenoma recurrence. Further information is available at www.vioxx.com.Rofecoxib is a selective cyclooxygenase-2 (COX-2) inhibitor previously licensed for treating acute and chronic pain; it was associated with fewer gastrointestinal adverse events than conventional NSAIDs. An earlier Cochrane review (Barden 2005) showed that rofecoxib is at least as effective as conventional non-steroidal anti-inflammatory drugs (NSAIDs) for postoperative pain. OBJECTIVES: To assess the analgesic efficacy and adverse effects of rofecoxib in single oral doses for moderate and severe postoperative pain. SEARCH STRATEGY: We searched Cochrane CENTRAL, MEDLINE, EMBASE and the Oxford Pain Relief Database for studies to June 2009. SELECTION CRITERIA: Randomised, double blind, placebo-controlled trials of single dose orally administered rofecoxib in adults with moderate to severe acute postoperative pain. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. Pain relief or pain intensity data were extracted and converted into the dichotomous outcome of number of participants with at least 50% pain relief over 4 to 6 hours, from which relative risk and number needed to treat to benefit (NNT) were calculated. Numbers of participants using rescue medication over specified time periods, and time to use of rescue medication, were sought as additional measures of efficacy. Information on adverse events and withdrawals was collected. MAIN RESULTS: Twenty new studies and seven from the earlier review met the inclusion criteria. Twenty-four studies were in dental surgery and three in other types of surgery. In total, 2636 participants were treated with rofecoxib 50 mg, 20 with rofecoxib 500 mg, and 1251 with placebo. The NNT for at least 50% pain relief over 4 to 6 hours with rofecoxib 50 mg was 2.2 (2.0 to 2.3) in all studies combined, 1.9 (1.8 to 2.0) in dental studies, and 6.8 (4.6 to 13) in other types of surgery. The median time to use of rescue medication was 14 hours for rofecoxib 50 mg and 2 hours for placebo. Significantly fewer participants used rescue medication following rofecoxib 50 mg than with placebo. Adverse events did not differ from placebo. AUTHORS' CONCLUSIONS: Rofecoxib 50 mg (two to four times the standard daily dose for chronic pain) is an effective single dose oral analgesic for acute postoperative pain in adults, with a relatively long duration of action.